Pressure mapping with textile sensors for compression therapy monitoring. (August 2016) - Baldoli, Ilaria; Mazzocchi, Tommaso; Paoletti, Clara; Ricotti, Leonardo; Salvo, Pietro; Dini, Valentina; Laschi, Cecilia; Francesco, Fabio Di; Menciassi, Arianna
Compression therapy is the cornerstone of treatment in the case of venous leg ulcers. The therapy outcome is strictly dependent on the pressure distribution produced by bandages along the lower limb length. To date, pressure monitoring has been carried out using sensors that present considerable drawbacks, such as single point instead of distributed sensing, no shape conformability, bulkiness and constraints on patient's movements. In this work, matrix textile sensing technologies were explored in terms of their ability to measure the sub-bandage pressure with a suitable temporal and spatial resolution. A multilayered textile matrix based on a piezoresistive sensing principle was developed, calibrated and tested with human subjects, with the aim of assessing real-time distributed pressure sensing at the skin/bandage interface. Experimental tests were carried out on three healthy volunteers, using two different bandage types, from among those most commonly used. Such tests allowed the trends of pressure distribution to be evaluated over time, both at rest and during daily life activities. Results revealed that the proposed device enables the dynamic assessment of compression mapping, with a suitable spatial and temporal resolution (20 mm and 10 Hz, respectively). In addition, the sensor is flexible and conformable, thus well accepted by the patient. Overall, this study demonstrates the adequacy of the proposed piezoresistive textile sensor for the real-time monitoring of bandage-based therapeutic treatments.